Plan de marketing para el posicionamiento del chocolate orgánico de la asociación “ASOPAPROPIE” en la provincia de Manabí - Cevallos Rendón, Cinthya Ramona (2019)
The globalization and high competitiveness of products and services are alert to market expectations, so the use of useful techniques and tools is vital. Under this perspective, the design of a marketing plan for the positioning of organic chocolate in the association "ASOPAPROPIE" in the province of Manabí becomes important. The deductive, inductive and analytical-synthetic method was used, supported by bibliographic and field research. In addition to the use of several techniques divided into: interview, survey, observation, SWOT. All of these were supported by tools such as: interview guide, PEST analysis, market segmentation, linear regression, five PORTER forces, competitive profile matrix, EFE matrix and EFI. With the application of the above, it was established that the main strength is to have a product of excellent quality, the strongest opportunity is the expansion to the national and international market. The weakness that most affects is the absence of technological processes and the main threat is the large existing chocolate companies. It was also determined that the main companies that rival the association are: Pascari, Salerito, Fortaleza del Valle and Nestlé. Therefore, it is concluded that the development of marketing strategies will allow the positioning of organic chocolate bars in the market, improve the financial profitability and administrative management of the association based on the differentiation of the product against the competition, standing out in the Organic characteristics, flavors and unique origin of chocolate bars.